Spatial and developmental heterogeneity of calcium signaling in olfactory ensheathing cells. Issue 3 (25th October 2012) - Thyssen, Anne; Stavermann, Maren; Buddrus, Kristina; Doengi, Michael; Ekberg, Jenny A.; St John, James A.; Deitmer, Joachim W.; Lohr, Christian
Abstract Olfactory ensheathing cells (OECs) are specialized glial cells in the mammalian olfactory system supporting growth of axons from the olfactory epithelium into the olfactory bulb. OECs in the olfactory bulb can be subdivided into OECs of the outer nerve layer and the inner nerve layer according to the expression of marker proteins and their location in the nerve layer. In the present study, we have used confocal calcium imaging of OECs in acute mouse brain slices and olfactory bulbs in toto to investigate physiological differences between OEC subpopulations. OECs in the outer nerve layer, but not the inner nerve layer, responded to glutamate, ATP, serotonin, dopamine, carbachol, and phenylephrine with increases in the cytosolic calcium concentration. The calcium responses consisted of a transient and a tonic component, the latter being mediated by store‐operated calcium entry. Calcium measurements in OECs during the first three postnatal weeks revealed a downregulation of mGluR1 and P2Y1 receptor‐mediated calcium signaling within the first 2 weeks, suggesting that the expression of these receptors is developmentally controlled. In addition, electrical stimulation of sensory axons evoked calcium signaling via mGluR1 and P2Y1 only in outer nerve layer OECs. Downregulation of the receptor‐mediated calcium responses in postnatal animals is reflected by a decrease in amplitude of stimulation‐evoked calcium transients in OECs from postnatal days 3 to 21. In summary, the results presented reveal striking differences in receptor responses during development and in axon–OEC communication between the two subpopulations of OECs in the olfactory bulb. © 2012 Wiley Periodicals, Inc.